National survey of research and development 2008: summary - Mohd. Asraf, Ratnawati; Sheikh Ahmad, Ismail; Mat Ghani, Gairuzazmi; Abu Kassim, Noor Lide (Malaysian Science and Technology Information Centre, 2009)
The 2008 Report on the National Survey of Research & Development was based on the survey carried out in 2006, which was the seventh survey of Research & Development (R&D) activities conducted in Malaysia. The National Survey of R&D is done once every two years and the analysis of the survey results provides an insight into the developments of R&D activities undertaken by the public and private sectors in Malaysia. Hence, this 2008 Report is the main source currently available to provide comprehensive information on the status of R&D activities in the country. It also includes data spanning 10 years so as to serve as a means to measure R&D growth in Malaysia.